Health-Related Quality of Life and the Desire for Revision Surgery Among Children With Cleft Lip and Palate. Issue 7 (October 2016) - Ranganathan, Kavitha; Shapiro, Danielle; Aliu, Oluseyi; Vercler, Christian J.; Baker, Michaella; Kasten, Steven J.; Warschausky, Seth A.; Buchman, Steven R.; Waljee, Jennifer F.
Abstract : Purpose: Children with cleft lip with or without palate (CLCP) require multiple reconstructive procedures, however, little is known about their desire for surgical revision. The purpose of this study was to examine the relationship between health-related quality of life (HRQOL) and the desire for revision. Methods: The authors surveyed children with CLCP (n = 71) and their caregivers regarding general and cleft-specific HRQOL and the desire for revision surgery. The authors used logistic regression models to evaluate the relationship between HRQOL and the desire for revision stratified by age, and determined the level of agreement between caregivers and children. Results: In this cohort, 54.9% of children desired revision, primarily of the nose (n = 23), lip (n = 20), and dentoalveolar structures (n = 19). Children 11 years or older were more likely to desire revision than younger children (OR 3.39, 95% CI [1.19, 9.67], P <0.05). Children who reported poorer HRQOL with respect to appearance (OR 2.31, 95% CI [1.25–4.29], P = 0.008), social development (OR 0.91, 95% CI [0.84–0.99], P = 0.02), and communication (OR 0.94, 95% CI [0.89–0.99], P = 0.02) were significantly more likely to desire revision than children who reported more positive HRQOL. Caregivers' and children's desires for revision were only modestly correlated ( r = 0.41). Conclusions: Children with CLCP who report poorer HRQOL are more likely to desire revision than children with higher HRQOL; these differences are further magnified among older children. Given the modest correlation between patient and caregiver goals for revision, it is important to evaluate both perspectives when considering revision surgery.